2022
DOI: 10.1016/j.isci.2021.103660
|View full text |Cite
|
Sign up to set email alerts
|

Gate-controlled gas sensor utilizing 1D–2D hybrid nanowires network

Abstract: Summary Novel gas sensors that work at room temperature are attracting attention due to their low energy consumption and stability in the presence of toxic gases. However, the development of sensing characteristics at room temperature is still a primary challenge. Diverse reaction pathways and low adsorption energy for gas molecules are required to fabricate a gas sensor that works at room temperature with high sensitivity, selectivity, and efficiency. Therefore, we enhanced the gas sensing performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In recent years, several ways of constructing SnO 2 /SnSe 2 heterostructures have been reported, such as partial oxidation of pristine SnSe 2 [ 17 ] and surface selenization of SnO 2 nanowires. [ 19 ] Additionally, the long‐term stability of hybrid SnO 2 /SnSe 2 has been confirmed theoretically and practically. However, there are still several issues that require further discussion and attention.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In recent years, several ways of constructing SnO 2 /SnSe 2 heterostructures have been reported, such as partial oxidation of pristine SnSe 2 [ 17 ] and surface selenization of SnO 2 nanowires. [ 19 ] Additionally, the long‐term stability of hybrid SnO 2 /SnSe 2 has been confirmed theoretically and practically. However, there are still several issues that require further discussion and attention.…”
Section: Introductionmentioning
confidence: 79%
“…To further enhance the gas sensing performance, constructing heterostructures in the SnSe 2 layered film, a new phase of SnO 2 has been confirmed to be an effective approach. [17][18][19] Considering NO 2 detection, studies have shown that an electron accumulation layer would form on the SnO 2 side close to the SnSe 2 /SnO 2 interface, trapping more adsorbed oxygen. During the NO 2 detection, the NO 2 molecules would interact with the adsorbed oxygen, which takes away more electrons and significantly enhances the response.…”
Section: Introductionmentioning
confidence: 99%
“…From this view, Seo et al fabricated an FET sensor using a 1D/2D hybrid nanowire network of SnO 2 /SnSe 2 and examined gas sensing behavior after applying different gate voltages. 85 The 2D SnSe 2 layer over the SnO 2 nanowire was synthesized by converting the shallow layer of SnO 2 into SnSe 2 using the CVD process (Fig. 11(g)).…”
Section: Van Der Waals Heterostructure Driven Gas Sensorsmentioning
confidence: 99%